1989
DOI: 10.1017/s0016672300027968
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of tasting in mice: VI. Saccharin, acesulfame, dulcin and sucrose

Abstract: Twenty-six strains of mice were tested for their reaction to four different sweet substances; saccharin, acesulfame, dulcin and sucrose. There was considerable strain variation in the degree to which they found the sweet substances preferable to water. The variation in preference for any one sweet substance is very highly correlated with the variation in preference for the other sweet substances. This is interpreted to mean that there is only one sweetness receptor, although an alternative explanation in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
102
2
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 11 publications
7
102
2
2
Order By: Relevance
“…Our finding that ethanol intake was higher in B6 than 129 mice is consistent with earlier results. 5 Consistent with our finding of a difference between the two strains in sucrose intake, there is evidence that B6 mice have higher intakes than do 129 mice of several sweet compounds, including sucrose, 10 saccharin, 5,10-12 acesulfame, dulcin, 10 glycine, 13 d-phenylalanine, and l-glutamine. 12 A positive relationship between alcohol intake and sweet solution intake has also been found among other inbred strains of mice 5 and rats, 3,4 and within F 2 hybrids from ethanolpreferring and ethanol-nonpreferring rat strains.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our finding that ethanol intake was higher in B6 than 129 mice is consistent with earlier results. 5 Consistent with our finding of a difference between the two strains in sucrose intake, there is evidence that B6 mice have higher intakes than do 129 mice of several sweet compounds, including sucrose, 10 saccharin, 5,10-12 acesulfame, dulcin, 10 glycine, 13 d-phenylalanine, and l-glutamine. 12 A positive relationship between alcohol intake and sweet solution intake has also been found among other inbred strains of mice 5 and rats, 3,4 and within F 2 hybrids from ethanolpreferring and ethanol-nonpreferring rat strains.…”
Section: Discussionsupporting
confidence: 82%
“…Although there still may have been interactions between solutions tested in this study, it seems unlikely that they would be sufficiently robust to affect the main conclusions about the direction of strain differences between B6 and 129 strains. Indeed, in our other experiments on these strains, 9,20,30 as well as in studies by other authors, 5,8,[10][11][12]15 B6 and 129 mice had the same character of differences in ethanol, sucrose, saccharin, citric acid, quinine, and NaCl consumption, regardless of whether the solutions were tested in the same or in different groups of animals.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Fuller (1974) demonstrated that most of the differences in saccharin preferences between C57BL/6J and DBA/2J strains depend on a single locus, Sac, with the dominant Sac b allele present in the C57BL/6J strain. Subsequent studies confirmed this finding in the BXD recombinant inbred strains, in crosses between the C57BL/6 and DBA/2 strains (Lush, 1989;Belknap et al, 1992;Phillips et al, 1994;Lush et al, 1995;Blizard et al, 1999) and in crosses between the C57BL/6ByJ and 129P3/J strains (Bachmanov et al, 1997). The Sac locus has been mapped to the subtelomeric region of mouse chromosome 4 (Phillips et al, 1994;Lush et al, 1995;Bachmanov et al, 1997;Blizard et al, 1999;Li et al, 2001) and more recently has been cloned positionally .…”
Section: Introductionmentioning
confidence: 74%
“…Mouse strains differ in their avidity to consume sweet solutions (Pelz et al, 1973;Stockton and Whitney, 1974;Ramirez and Fuller, 1976;Lush, 1989). Fuller (1974) demonstrated that most of the differences in saccharin preferences between C57BL/6J and DBA/2J strains depend on a single locus, Sac, with the dominant Sac b allele present in the C57BL/6J strain.…”
Section: Introductionmentioning
confidence: 99%